Simultaneous determination of zidebactam and cefepime in dog plasma by LC–MS/MS and its application to pre‐clinical pharmacokinetic study. (24th April 2018) - Patil, Kiran; Tambe, Harshad; Zope, Vineet; Chavan, Rajesh; Yeole, Ravindra; Patel, Mahesh
Abstract: A precise and accurate liquid chromatography–tandem mass spectrometric (LC–MS/MS) bioanalytical method has been developed and validated for the simultaneous quantification of zidebactam (ZID) and cefepime (FEP) in dog plasma. Ceftazidime was used as an internal standard. Protein precipitation method was used as sample preparation approach. The calibration curve obtained was linear ( r ≥ 0.99) over the concentration range 0.156–80 μg/mL for ZID and 0.312–160 μg/mL for FEP. The method was validated as per US Food and Drug Administration guidelines and the results met the acceptance criteria. A run time of 3.5 min for each sample made it possible to analyze the maximum number of samples per day. The proposed method was successfully applied for pharmacokinetic study in beagle dogs.